Urodynamic Study in Voiding Dysfunction in Young Adults - Yadav, Deepak Kumar; Adhikari, Mahesh Bahadur; Maharjan, Bipin; Gautam, Ravi Kiran; Mishra, Prashant; Shrestha, Pramesh Prasad; Khadga, Ajit; Ghimire, Subodh (Nepal Mediciti Medical Journal, 2025)
BACKGROUND Voiding dysfunction defined by the International Continence Society and International Urogynecological Association as“abnormal, slow, and/or incomplete micturition” as diagnosed by symptoms and urodynamic investigations. Chronic Lower Urinary Tract Symptoms (LUTS) in young men are often misdiagnosed. Urodynamic evaluation is very useful in establishing the correct diagnosis and ultimately in delivery of appropriate therapy. This study utilizes Urodynamic study (UDS) for diagnosis of voiding dysfunctions and help in proper treatment. METHODS The study was conducted in Nepal Mediciti Hospital, Lalitpur Nepal in 2024. Urodynamic study (UDS) of 148 young adults 40 years of age or less with chronic voiding dysfunction, were performed and analyzed prospectively to identify the etiology. RESULTS Out of 148 patients, 122 (82.4%) were male and 26 (17.6%) were female. The most common disorder diagnosed after urodynamic study (UDS) was Detrusor Underactivity seen in 46 (31.1%) followed by Neurogenic Bladder seen in 17(11.5%). CONCLUSIONS While the exact causes of voiding dysfunction in young men remain unclear, it is a common issue. Uroflowmetry provides a valuable screening tool for patients experiencing symptoms. UDS can diagnose various Lower Urinary Tract diseases and appear to influence treatment decisions made by clinicians in determining treatment pathways.